Delicate edible birds and other stories - Groff, Lauren (Hachette Books, 2015)
Groff follows up The Monsters of Templeton with this innovative and beautifully written collection that covers a wide swath of humanity, from east coast resort towns, to the early 20th century flu epidemic, to WWII Europe.